Family Support for the Quality of Life of Plwha at the Vct Polyclinic - Lisma Natalia Br Sembiring; Crystin E. Watunglawar; Fathia I.Said; Adriana Sainafat; Yance R. Rairuny; Yestiani N. Joni (Journal La Medihealtico, 2025)
The increase in people with HIV/AIDS (ODHA) has a negative impact on society. One of the impacts that often occurs in ODHA is self-esteem caused by stigma and discrimination from society so that family support is needed to help eliminate stigma and discrimination from society so that ODHA can be confident, can accept their condition, and are enthusiastic in living life . to determine the relationship between family support and quality of life in ODHA at the Sentani Community Health Center Polyclinic. This type of research is descriptive quantitative conducted in July 2025, with a sample of 56 respondents with a non-probability sampling method. Data were obtained using questionnaires and analyzed univariately and bivariately using Somer's D statistical tests. It was found that 31 respondents had high family support and 25 respondents had low support and 30 respondents had good quality of life and 26 respondents had low quality of life. So the results of the Somer's D statistical test obtained a P-Value of 0.019 <0.05. Family support for ODHA patients has a high support category and quality of life in ODHA patients has a good quality of life category. This shows that there is a significant influence between family support on the quality of life of patients undergoing treatment at the Sentani Community Health Center Polyclinic. By increasing public insight, the stigma obtained by ODHA related to their disease can be reduced. So that families who have family members with HIV/AIDS problems can provide attention and support to their family members who are undergoing treatment.